2006
DOI: 10.1002/elps.200500736
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of macrophages stimulated by lipopolysaccharide: Lipopolysaccharide inhibits the cleavage of nucleophosmin

Abstract: Lipopolysaccharide (LPS) is a complex glycolipid composed of a hydrophilic polysaccharide and a hydrophobic domain that is responsible for the biological activity of LPS. There are many reports about LPS stimulation, and many activated proteins have been detected after LPS stimulation in various cell types. Furthermore, most of the LPS signaling pathways are clear. However, we were interested in examining the changes of LPS-induced total cytosolic proteins expression and the LPS signaling pathway by the proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Several examples are provided. Nucleolin (NCL), a protein involved in the synthesis and maturation of ribosomes, is 2.4 fold increased at mRNA level but 29 times decreased at protein level, which corresponds to a trend observed previously 30, suggesting a selective degradation of this protein after LPS stimulation. In addition, the endogenous amount of lipocalin 2 (LCN2), a secretive protein important to antibacterial innate immune response 31 and known to be induced by LPS 32, was decreased by 3-fold, despite of a 6 fold increase of mRNA.…”
Section: Discussionsupporting
confidence: 86%
“…Several examples are provided. Nucleolin (NCL), a protein involved in the synthesis and maturation of ribosomes, is 2.4 fold increased at mRNA level but 29 times decreased at protein level, which corresponds to a trend observed previously 30, suggesting a selective degradation of this protein after LPS stimulation. In addition, the endogenous amount of lipocalin 2 (LCN2), a secretive protein important to antibacterial innate immune response 31 and known to be induced by LPS 32, was decreased by 3-fold, despite of a 6 fold increase of mRNA.…”
Section: Discussionsupporting
confidence: 86%
“…This led to the identification of a larger number of changing proteins in this model system than in previous studies (11,(15)(16)(17)(18)39). One exception is a study by Du et al (39), who identified Ͼ700 differentially expressed proteins after 10 min of LPS stimulation among 2144 detected proteins.…”
Section: Discussionmentioning
confidence: 85%
“…Proteomics studies on the LPS response of murine macrophages have been performed in a few older studies [22,23,41], but at that time 2-DE patterns were characterised solely by physicochemical properties of the obtained spots (pI, M r ). More recent studies including identification of intracellular LPS responsive proteins employed cell lines rather than primary cells and, in addition, used different comparative 2-DE approaches [42][43][44]. Accordingly, the sets of proteins identified show generally little overlap with ours.…”
Section: Discussionmentioning
confidence: 94%